2020
DOI: 10.1002/jimd.12344
|View full text |Cite
|
Sign up to set email alerts
|

Combined proteomic and lipidomic studies in Pompe disease allow a better disease mechanism understanding

Abstract: Pompe disease (PD) is caused by deficiency of the enzyme acid α‐glucosidase resulting in glycogen accumulation in lysosomes. Clinical symptoms include skeletal myopathy, respiratory failure, and cardiac hypertrophy. We studied plasma proteomic and lipidomic profiles in 12 PD patients compared to age‐matched controls. The proteomic profiles were analyzed by nLC‐MS/MS SWATH method. Wide‐targeted lipidomic analysis was performed by LC‐IMS/MS, allowing to quantify >1100 lipid species, spanning 13 classes. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The multiplexed profiling in serum, like untargeted multi‐omics based on liquid/gas‐phase MS techniques, has been extensively studied for precision disease diagnosis. [ 31 ] These techniques need to combine different sample treatment protocols (e.g., protein precipitation, desalting, digestion, and chromatography separation), leading to a low analysis throughput of ≈hours per sample and a large volume of ≈10 to 500 µL per workflow. By comparison, the advantages of our approach could be mainly concluded into two aspects: 1) every single apparatus in the multiplexed platform enjoys a fast response time (≈second per sample) for high‐throughput detection; 2) the sampling and analysis process for LDI‐MS and SERS are easy‐operation and highly compatible with each other.…”
Section: Resultsmentioning
confidence: 99%
“…The multiplexed profiling in serum, like untargeted multi‐omics based on liquid/gas‐phase MS techniques, has been extensively studied for precision disease diagnosis. [ 31 ] These techniques need to combine different sample treatment protocols (e.g., protein precipitation, desalting, digestion, and chromatography separation), leading to a low analysis throughput of ≈hours per sample and a large volume of ≈10 to 500 µL per workflow. By comparison, the advantages of our approach could be mainly concluded into two aspects: 1) every single apparatus in the multiplexed platform enjoys a fast response time (≈second per sample) for high‐throughput detection; 2) the sampling and analysis process for LDI‐MS and SERS are easy‐operation and highly compatible with each other.…”
Section: Resultsmentioning
confidence: 99%
“…To precisely decipher the effects of ERT on muscle tissue, proteomic analyses have been adopted based both on our experience in proteomics of skeletal muscle from patients and healthy subjects under various conditions [26][27][28][29][30][31][32], and on literature reports [33,34]. More specifically, a double proteomic approach has been applied based on two-dimensional difference gel electrophoresis (2D-DIGE) and label-free liquid chromatography-mass spec-trometry (LC-MS/MS) analyses to determine both differential abundance of intact proteoforms and of trypsin digested proteins in muscle extracts of LOPD patients before and after 12 months of ERT.…”
Section: Introductionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is one of the most extensively used clinical tumor markers (Agrawal et al, 2020; Farahani et al, 2020; Grunnet & Sorensen, 2012; Sidorina et al, 2021), which is upregulated in advanced colorectal cancer by approximately 90% (Yamamoto et al, 2005). CEA is attached to the surface of cell membrane via GPI anchor, thus the membrane‐bound CEA can be cleaved by GPLD1 (Bramswig et al, 2013).…”
Section: Roles Of Gpld1 In Chronic Diseasesmentioning
confidence: 99%
“…Pompe disease (PD), also named as glycogen storage disease type II, is caused by the lack or deficiency of the lysosomal enzyme acid a-glucosidase, thereby resulting in severe cardiac and skeletal muscle myopathy or respiratory failure due to the progressive accumulation of glycogen (Meena & Raben, 2020). One of the studies has demonstrated that decreased GPLD1 level is significantly associated with the lipids disorders with acyl-chain characteristics of GPI-anchor structure in PD patients, suggesting the potential involvement of GPI-anchor system in PD (Sidorina et al, 2021).…”
Section: The Role Of Gpld1 In Glucose Metabolismmentioning
confidence: 99%